Effect of SGLT2 inhibitors on the proteinuria reduction in patients with IgA nephropathy - Dong, Yaping; Shi, Sufang; Liu, Lijun; Zhou, Xujie; Lv, Jicheng; Zhang, Hong (Frontiers in Medicine, 2023)
Backgroud: Recent trials suggest sodium-glucose cotransporter 2 inhibitors (SGLT2i) significantly reduced proteinuria in patients with IgA nephropathy (IgAN). While little was known its efficacy in clinical practice especially in those already received full dose RAAS inhibitors.A cohort of 93 Chinese patients with biopsy-proven IgAN and persistent proteinuria underwent full supportive therapy, including optimal blood pressure control and full dose angiotensin-converting enzyme-inhibitor or angiotensin receptor blocker therapy. Proteinuria reduction at three and six months after initiating SGLT2i therapy was analyzed.Results: A total of 93 patients were enrolled in this study and 62 of them completed the six-month follow-up. After SGLT2i administration, a significant reduction in proteinuria was observed, with a decrease of 22.9% (P<0.001) at three months and 27.1% (P<0.001) at six months. During the sixmonth follow-up period, a decline of 3.0 ml/min/1.73m² in estimated glomerular filtration rate (eGFR) (P=0.012) and an increase of 0.8 g/L in albumin (P=0.017) were observed. The antihypertensive effect of SGLT2i was not significant (P>0.05). Notably, a consistent antiproteinuric effect of SGLT2i was observed across various settings, including different age groups, baseline levels of proteinuria/eGFR, use of immunosuppressive agents, and the presence of comorbid diabetes and hypertension (all P values > 0.05). This is a provisional file, not the final typeset articleThe proteinuria was significantly reduced after SGLT2i administration in IgAN patients with full dose angiotensin-converting enzyme-inhibitor or angiotensin receptor blocker therapy. Importantly, the antiproteinuric effect of SGLT2i was observed independently of immunosuppressive agent therapy, age, baseline eGFR and proteinuria levels, as well as the history of hypertension and diabetes.